Melioidosis in Pahang, Malaysia - How, Soon Hin; Ng, K H; Ab Rahman, Jamalludin; Shah, Anis; Rathor, Mohammad Yousuf (Malaysian Medical Association, 2005)
We conducted a retrospective review of 135 patients with melioidosis in Pahang from January 2000 to June 2003. Patients were mostly male (78.5%) and Malay (83%) with a median age of 51 years. Seventy four percent of patients were diabetic. Common presentations were pneumonia (40.7%), septicaemic without obvious source of infection (19.3%) and multiple organ involvement (15.6%). Only 32.7% were given appropriate antibiotics empirically. The overall mortality was 54% with most deaths (65%) occurring within 48 hours of admission. Patients with pneumonia, multiple organ involvement and septicaemic of unknown source had higher mortality as compared to patients with subcutaneous, musculoskeletal or single internal organ involvement without pneumonia (p < 0.001). The relapse rate was 19.2%.